The Bahamas : 2001 Article IV Consultation-Staff Report and Public Information Notice. (IMF Staff Country Reports; Country Report, 2001)
The Bahamian economy has experienced a sustained growth led by substantial inflows of foreign investment in tourism, shipping, and construction, and a steady expansion of financial services. Executive Directors commended the sound macroeconomic policies and the decline in unemployment, and emphasized the need for maintaining a prudent fiscal stance, enhancing competitiveness, and accelerating structural reforms. They commended the progress in eliminating the central government deficit and money laundering, and stressed the need to strengthen the country's statistical base.